Rare Anaemias, Sickle-Cell Disease and COVID-19 - Vives Corrons , Joan-Lluis (Acta Biomedica Atenei Parmensis, 2020)
For rare haematological diseases (RHD), the first question to be answered is if patients with be- nign red blood cell (RBC) defects like haemoglobinopathies, membranopathies and enzymopathies are more vulnerable to COVID-19 infection. Up to now, there is no yet literature on the subject, but, like in general population, the presence of comorbidities such as diabetes, heart disease, pulmonary hypertension, reduced kidney and/or liver function, worsen the effects of the infection. Splenectomy may be an additional risk factor.